Transmission Error Analysis of Cycloid Pin Wheel Based on Geometric Contact Algorithm - Huang Yuelei; Zhang Yinghui; He Weidong (Jixie chuandong, 2024)
In response to the problem that the error value is usually set as a constant value in the tooth contact analysis (TCA) model of cycloidal needle tooth transmission, which makes the calculation results unreasonable, and the calculation does not converge in the calculation process, an analysis model of cycloidal pinwheel transmission error including multi-factors such as shaping modification and processing error is established. After analyzing the vector equation of the meshing point, a method to solve the problem of numerical non-convergence is proposed, that is, to find the meshing point with equal normal vector in the obtained point with equal ordinate and abscissa on the cycloid wheel and the needle tooth. After analyzing the form of the rotary body error, a method to solve the unreasonable calculation results is proposed, that is, the cycloid circumferential joint error, the cycloid tooth profile radial runout error and the needle tooth center circle radius error change periodically in the tolerance band. RV-80E reducer is taken as the test object, and the correctness of the theoretical model is verified by comparing the test results. The influence of each error on the transmission error is studied, and the sensitivity analysis of each error is carried out. The results show that the needle tooth radius error and the normal clearance under the comprehensive action of the needle tooth and the needle tooth shell gap are the important factors affecting the transmission error.